The Evaluation For Accuracy of Ultrasonic Non-Destructive Testing In Measuring Thickness on Dissimilar Material By Using A1207 Pen-gauge - Mahzan, Shahruddin; Roger, Babie Jane (Research Progress in Mechanical and Manufacturing Engineering, 2023)
During pre-service and in-service inspections, ultrasonic thickness measurement (UTM) is critical for ensuring the integrity and dependability of components, structures, and plants. In general, all measurements are subject to error, which adds to the result's uncertainty. Errors can be classified as either human or technical. The components perform as expected for the duration of their expected useful lives because they have been put through their paces in terms of UTM. This study looks at how a portable thickness gauge A1207 Pengauge compares to a vernier caliper and ruler in terms of performance of precision, accuracy, sensitivity, and ability to achieve the desired result when determining material thickness. In this research, the recording devices were used to record the before and after calibration thickness. The calculated velocity was then applied to the experimental specimens which are carbon steel and aluminium plate. The results show that the UTM method has been demonstrated as accurately as calipers when measuring the thickness of any material in any situation. UTM produces the closest response to the actual measurement even without access on either side.